Public transportation in Cartagena, Colombia : understanding preferences using discrete choice models (2013)
This paper revisits the data set collected by Toro, Alvis and Arellano (2005) in order to evaluated three main models in transportation: probit, conditional logit, and the nested logit. The results show that the advantages of other transportation modes over buses are their lower travel and waiting times. Additionally, it was found that a traveler facing equal times and cost would prefer bus rather than other alternatives